Beating of a Spherical Liquid Crystal Elastomer Balloon under Periodic Illumination - Wenyan Cheng; Quanbao Cheng; Changshen Du; Yuntong Dai; Kai Li (Micromachines, 2022)
Periodic excitation is a relatively simple and common active control mode. Owing to the advantages of direct access to environmental energy and controllability under periodic illumination, it enjoys broad prospects for application in soft robotics and opto-mechanical energy conversion systems. More new oscillating systems need to be excavated to meet the various application requirements. A spherical liquid crystal elastomer (LCE) balloon model driven by periodic illumination is proposed and its periodic beating is studied theoretically. Based on the existing dynamic LCE model and the ideal gas model, the governing equation of motion for the LCE balloon is established. The numerical calculations show that periodic illumination can cause periodic beating of the LCE balloon, and the beating period of the LCE balloon depends on the illumination period. For the maximum steady-state amplitude of the beating, there exists an optimum illumination period and illumination time rate. The optimal illumination period is proved to be equivalent to the natural period of balloon oscillation. The effect of system parameters on beating amplitude are also studied. The amplitude is mainly affected by light intensity, contraction coefficient, amount of gaseous substance, volume of LCE balloon, mass density, external pressure, and damping coefficient, but not the initial velocity. It is expected that the beating LCE balloon will be suitable for the design of light-powered machines including engines, prosthetic blood pumps, aircraft, and swimmers.